Pure Large Cell Neuroendocrine Carcinoma of Ovary: A Rare Clinical Entity and Review of Literature - P. N. Shakuntala; K. Uma Devi; K. Shobha; U. D. Bafna; M. Geetashree (Case Reports in Oncological Medicine)
Large cell neuroendocrine carcinoma (LCNEC) of the ovary is a rare tumor and is now included in the World Health Organization tumor classification. Its prognosis is generally very poor even when the diagnosis is made at an early stage. We report a case of pure large cell neuroendocrine tumour of ovary, appearing 9 months following laparoscopic type I hysterectomy, bilateral pelvic lymph node dissection with ovarian preservation of anatomically normal looking ovaries performed for a cervical biopsy diagnosis of cervical intraepithelial neoplasia grade III with foci of invasion. The rarity lies in the rapid onset (9 months) of a large tumor following conservation of an anatomically normal ovaries. Surgical debulking and five cycles of chemotherapy (Etoposide and Cisplatin) were administered to the woman. She is on followup with no clinical or radiological evidence of disease recurrence for 6 months.